COUNTERMEASURE FOR MINIMIZE UNWANTED ALARM OF AUTOMATIC FIRE NOTIFICATION SYSTEM IN THE REPUBLIC OF KOREA - Hasung Kong (Модернизация, инновация, развитие, 2015)
In this article investigated the cause of error through survey to building officials for minimizing the unwanted alarm of automatic fire notification and suggested countermeasure for minimizing the unwanted alarm. The main cause of the unwanted alarm is defective fire detector, interlocking with automatic fire detection system, lack in fire safety warden’s ability, worn-out fire detect receiving system. The countermeasure for minimizing unwanted alarm is firstly, tightening up the standard of model approval, Secondly, interlocking with cross-section circuit method fire extinguishing system or realizing automatic fire notification system interlocking with home network, thirdly, tightening up licensing examination of fire safety warden, lastly, it suggested term of use rule of fire detect receiving system.